2016
DOI: 10.1890/14-1990
|View full text |Cite
|
Sign up to set email alerts
|

Improved estimation of intrinsic growthrmaxfor long‐lived species: integrating matrix models and allometry

Abstract: Intrinsic population growth rate (r(max)) is an important parameter for many ecological applications, such as population risk assessment and harvest management. However, r(max) can be a difficult parameter to estimate, particularly for long-lived species, for which appropriate life table data or abundance time series are typically not obtainable. We describe a method for improving estimates of r(max) for long-lived species by integrating life-history theory (allometric models) and population-specific demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Differences between methods 2, 3 and 6 and methods 4 and 5 were more accentuated for fast-growing populations, suggesting that the ad hoc treatment or omission of fecundity in methods 4 and 5, respectively, can have a large effect on estimates. It is also important to note that Method 5, which is based on allometric scaling relationships, will underestimate r max if optimal survival is overestimated, whereas Method 6 (the Euler-Lotka equation) and its derivations (methods 2 and 3) will overestimate r max if optimal survival is overestimated, which points to the fact that either of these methods (allometric vs. demographic models) should probably not be used alone (Dillingham et al 2016). A recent expansion of the DIM method that draws strength from both allometric and life table models (Dillingham et al 2016) has the potential to generate improved estimates and more realistic depictions of uncertainty in the population growth rate and could thus be tested across a variety of populations with different life histories to provide improved conservation and management advice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences between methods 2, 3 and 6 and methods 4 and 5 were more accentuated for fast-growing populations, suggesting that the ad hoc treatment or omission of fecundity in methods 4 and 5, respectively, can have a large effect on estimates. It is also important to note that Method 5, which is based on allometric scaling relationships, will underestimate r max if optimal survival is overestimated, whereas Method 6 (the Euler-Lotka equation) and its derivations (methods 2 and 3) will overestimate r max if optimal survival is overestimated, which points to the fact that either of these methods (allometric vs. demographic models) should probably not be used alone (Dillingham et al 2016). A recent expansion of the DIM method that draws strength from both allometric and life table models (Dillingham et al 2016) has the potential to generate improved estimates and more realistic depictions of uncertainty in the population growth rate and could thus be tested across a variety of populations with different life histories to provide improved conservation and management advice.…”
Section: Discussionmentioning
confidence: 99%
“…and can be solved iteratively. Niel & Lebreton (2005) found that a rT % 1 for birds and Dillingham et al (2016) recently found that a rT % 1 for several vertebrate taxa (birds, mammals and elasmobranchs); thus, r max can be obtained from knowledge of a and s only.…”
Section: I M : M E T H O Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Population growth rates represent the population-specific intrinsic rate of increase, or the per-capita rate to which a particular population is capable of increasing under optimum environmental conditions (Huston, 1979). An intrinsic population growth rate is a difficult parameter to estimate, especially in long-lived species such as sturgeons (Dillingham et al, 2016). Reflecting the lack of consensus on the probable intrinsic population growth rate in sturgeons and paddlefish, the majority of respondents (53%) were unsure of the proper response, indicating that the population growth rate concept is not fully comprehended within the scientific community.…”
Section: Population Growth Ratementioning
confidence: 99%
“…of Commerce 2001) and population viability analyses (Merrick & Haas, 2008;Snover & Heppell, 2009). For many long-lived and late-maturing species, the maximum rate of population growth is unknown or inestimable using direct methods (e.g., analysis of trends in abundance indices) because of data limitations (Dillingham et al, 2016). In such cases, demographic models, such as life tables and projection matrices, are used to represent population dynamics and to generate estimates of population growth (Caswell, 2001;Zerbini, Clapham, & Wade, 2010).…”
Section: Introductionmentioning
confidence: 99%